The Relationship Between Characteristic of Tuberculosis Patient with Compliance in Check a Sputum During Treatment - Dea Nurma Ruditya (Universitas Airlangga, 2015)
Pulmonary TB disease in Indonesia is one of the national priority for disease control programs. The success of the TB eradication program known through achieving TB control indicators. Cure rate and treatment success in the Puskesmas Tanah Kalikedinding still not reached the target. This research aims to determine the factors associated with patient compliance in examined sputum for TB treatment at the Puskesmas Tanah Kalikedinding Surabaya. This research using an  observational  analytic  cross  sectional  design.  Data  obtained  on 38  respondents  BTA positive pulmonary TB (category 1) aged 15-65 years who have completed treatment for 6 months from January 2012 to June 2013. Sampling used simple random sampling techniques. Questionnaires are used to identify the characteristics, knowledge levels, PMO support and compliance in check a sputum during treatment. Data were analyzed using chi square test and bifilar logistic regression with a significance level (α) of 5%. Age (p = 0,699), gender (p = 0,446), education level (p = 0,712), employment status (p = 1,00), income level (p = 0,48), support the PMO (p = 0,65) and the affordability range of health services (p = 0,65) do not relate to compliance in check a sputum during treatment. Home visit by health staff need to be done for noncompliance patient of sputum checking and make further research in health service factor. Keywords: compliance, sputum examination, characteristic, Pulmonary Tuberculosis